Direct interaction of FliX and FlbD is required for their regulatory activity in Caulobacter crescentus - Dutton Rachel J; Xu Zhaohui; Gober James W (BMC Microbiology, 2011)
Abstract Background The temporal and spatial expression of late flagellar genes in Caulobacter crescentus is activated by the transcription factor FlbD and its partner trans-acting factor FliX. The physical interaction of these two proteins represents an alternative mechanism for regulating the activity of σ54 transcription factors. This study is to characterize the interaction of the two proteins and the consequences of the interaction on their regulatory activity. Results FliX and FlbD form stable complexes, which can stand the interference of 2.65 M NaCl. The stability of FliX and FlbD was affected by the co-existence of each other. Five FliX mutants (R71A, L85K, Δ117-118, T130L, and L136K) were created by site-directed mutagenesis in conserved regions of the protein. All mutants were successfully expressed in both wild-type and ΔfliX Caulobacter strains. All but FliXL85K could rescue the motility and cell division defects of a ΔfliX mutant strain. The ability of FliX to regulate the transcription of class II and class III/IV flagellar promoters was fully diminished due to the L85K mutation. Co-immunoprecipitation experiment revealed that FliXL85K was unable to physically interact with FlbD. Conclusions FliX interacts with FlbD and thereby directly regulates the activity of FlbD in response to flagellar assembly. Mutations in highly conserved regions of FliX could severely affect the recognition between FliX and FlbD and hence interrupt the normal progression of flagellar synthesis and other developmental events in Caulobacter.